KIAT AYAH MENGHARMONISKAN HUBUNGAN DENGAN ANAK DI ERA DIGITAL - Kosma Manurung (FILADELFIA: Jurnal Teologi dan Pendidikan Kristen, 2023)
The harmony of a true relationship is the dream of everyone, both those who are building relationships and those who are going to build relationships. Even fathers deep down crave a harmonious relationship with their children. Unfortunately, due to various reasons or actions that were born from a lack of understanding, the father and son's relationship was not harmonious. This article intends to offer tips that fathers can apply in harmonizing relationships with their children in the digital era. By using a qualitative narrative method and supported by literature review, it is hoped that it will be able to provide a careful and in-depth picture of narratives about the harmony of fathers and children in the Bible, the existence of children in the digital era, and father's tips in harmonizing relationships with their children. It was concluded that in order to harmonize the relationship with their children, fathers need to introduce harmony in their family, make their family an example of this harmony, make this a entrenched habit in the family, and the father becomes the main instrument in teaching and exemplifying harmony.Keharmonisan hubungan sejatinya menjadi dambaan setiap orang baik yang sedang membangun hubungan maupun yang akan membangun hubungan. Para ayah pun jauh di kedalaman hatinya mendambakan hubungan yang harmonis dengan anak-anaknya. Sayangnya karena berbagai alasan ataupun tindakan yang lahir dari kurangnya pemahaman menyebabkan hubungan ayah dan anaknya menjadi tidak harmonis. Artikel ini bermaksud menawarkan kiat yang bisa ayah terapkan dalam mengharmoniskan hubungan dengan anaknya di era digital. Dengan menggunakan metode kualitatif naratif dan dukungan kajian literatur diharapkan mampu memberikan gambaran yang cermat dan mendalam terkait narasi tentang keharmonisan ayah dan anak di Alkitab, keberadaan anak di era digital, serta kiat ayah dalam mengharmoniskan hubungan dengan anaknya. Disimpulkan bahwa untuk mengharmoniskan hubungan dengan anaknya maka para ayah perlu memperkenalkan keharmonisan di tengah keluarganya, menjadikan keluarganya contoh keharmonisan tersebut, menjadikan hal ini kebiasaan yang membudaya di keluarga, serta sang ayah menjadi istrumen utama dalam mengajarkan maupun mencontohkan keharmonisan.